Concept of competitiveness in small business - Navruz-zoda Leyli Bakhtiyorovna, (THE INNOVATION ECONOMY, 2026)
This article provides an in-depth theoretical and practical analysis of the concept of enhancing the competitiveness of small businesses. Within the framework of the “Uzbekistan–2030” strategy, the economic, social, and innovative potential of the small business sector is comprehensively studied. The research is based on international approaches such as Michael Porter’s Five Forces Model, Jay Barney’s Resource-Based View (RBV), and David Teece’s theory of Dynamic Capabilities. Moreover, the scientific works of leading Uzbek scholars — M.R. Boltabayev, M.S. Qosimova, B.K. G‘oyibnazarov, Sh.J. Ergashkhodjayeva, A.N. Samadov, Sh.I. Otajonov, A.Sh. Toshpo‘latov, I.I. Umaraliyev, and Q.Kh. Abdurakhmanov — are extensively utilized. Local scholars have thoroughly analyzed the role of small business entities in the economic environment, the factors shaping competitive advantage, marketing and innovation strategies, state support, and regional development. Based on these theoretical and practical findings, indicators, evaluation criteria, and strategic directions aimed at developing small business are proposed. The article also presents data and practical recommendations concerning the share of small business in Uzbekistan’s GDP, its role in employment, and its contribution to innovation implementation.